Globalization and Chinese Culture (Based on the Works of Chinese Scientists) - Chi Qingzho; R. A. Nurtazinab (Евразийская интеграция: экономика, право, политика, 2023)
The research is aimed at s tudying the works of Chinese authors on the influence of globalism on Chinese culture.Aim. To identify the peculiarities of the interpretation of Chinese researchers of the influence of modern global processes on traditional Chinese culture.Tasks. To determine the techniques used by Chinese authors in the interpretation of globalization and its impact on traditional Chinese culture.Methods. Historical, political, and sociological research methods were used to determine the specifics of the Chinese understanding of global processes and their impact on culture.Results. Chinese researchers adhere to the position that explains that diversity and the unity of culture are two inseparable aspects of the development of cultural diversity in the modern world. Therefore, in the context of globalization, it is necessary not only to adhere to the principle of the unity of culture as a universal phenomenon, but also to increase tolerance for cultural diversity, based on the principle of preserving each original culture, which, to varying degrees, are today affected by globalization processes.Conclusions. For Chinese researchers in the context of globalization, the problem of cultural diversity, firstly, is an important universal factor that must be preserved. Secondly, the diversity of cultures is a condition for preserving one’s own, Chinese traditional culture. Thirdly, traditional Chinese culture in modern China has become a new ideology in state administration, which contributes to the modernization of the country. Fourth, the preservation and development of traditional Chinese culture has a positive effect on China’s rapid economic growth.